Process development and commissioning of a bioreactor for mass culturing of USAB granules by process induction and microbial stimulation - Van Zyl, Pierrie Jacobus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2005.